PLAYING AND PRODUCING CULTURE IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2011)
The intent of this article is to share the work of the Unit Municipal Kindergarten Mac, the Municipal School of Belem-Pa, in 2010. This work is based on theoretical studies of childhood pedagogy and on the play with Junqueira Filho (2006), Gallardin (1996), Bomdioli & Mantovani (1998), Winnicott (1975), Benjamin (2002), Wallon (2000) . The methodological approach consisted of the curriculum from the various languages of the child, which involves construction of projects host Olympic games of projects, involving classes bimonthly coordinator / teachers / children and families which aimed to contribute to the process of interaction and socialization between and all classes of context, to aggregate the social, cultural and human resources through playful learning situations with fun and games in favor of a full development of the child. The relevant aspects found from this methodological organization, lie in the valuation of different childhoods, children's perceived role in the children at play and playfulness of recovery, building a more humane Childhood Education emphasizing the educational process and pedagogical environments and host and sharing, which allows playing various inserts and reads the world as well, can translate into a commitment of educators in planning and organizing spaces more playful and interactive educational environment for children.
Keywords: Leadership of the child; Jokes; Exploitation of Children; playfulness